О мятеже на тихом Иже. Год 1918-й: [документально-художественный очерк] / Евгений Шумилов - Шумилов Евгений Федорович (Удмуртия, 2018)
К 100-летию трагедии на Иже Экземпляры: ф.2 (20200917) / Инвентарный номер: 60285 / Цена: / Сис.шифр: 63.3(2Рос.Удм) / Авт.знак: Ш 96 / ГРНТИ: 03.23.55 / ББК: 63.3(2Рос.Удм)